The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11203307
|View full text |Cite
|
Sign up to set email alerts
|

Flaxseed Bioactive Compounds: Chemical Composition, Functional Properties, Food Applications and Health Benefits-Related Gut Microbes

Abstract: Flaxseed (Linum usitatissimum L.) has gained worldwide recognition as a health food because of its abundance in diverse nutrients and bioactive compounds such as oil, fatty acids, proteins, peptides, fiber, lignans, carbohydrates, mucilage, and micronutrients. These constituents attribute a multitude of beneficial properties to flaxseed that makes its use possible in various applications, such as nutraceuticals, food products, cosmetics, and biomaterials. The importance of these flaxseed components has also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 148 publications
0
31
0
Order By: Relevance
“…Flaxseed ( Linum usitatissimum L.) is one of the crucial oilseeds [ 1 ], which is a source of oil rich in essential n-3 fatty acids (α-linolenic acid, ALA). Flaxseed, as well as flaxseed cakes or meals, products remaining after pressing flaxseed oil, are also a source of various compounds, such as proteins, mucilage and lignans [ 2 ]. These compounds can be valuable for food production from both nutritional and functional points of view [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flaxseed ( Linum usitatissimum L.) is one of the crucial oilseeds [ 1 ], which is a source of oil rich in essential n-3 fatty acids (α-linolenic acid, ALA). Flaxseed, as well as flaxseed cakes or meals, products remaining after pressing flaxseed oil, are also a source of various compounds, such as proteins, mucilage and lignans [ 2 ]. These compounds can be valuable for food production from both nutritional and functional points of view [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the presence of water-soluble proteins in food also enhances the overall functional properties, namely, emulsification, foaming, water absorption capacities, and oil absorption capacities. Hence, water-soluble proteins provide valuable information on the overall nutritional and functional properties of food and can also help in optimizing a definite food processing technique in the food production process . In our study, the water-soluble protein content was observed to significantly increase ( p < 0.05) in flour samples from 0 min (untreated) to 15 min exposure time.…”
Section: Resultsmentioning
confidence: 50%
“…Technol. XXXX, XXX, XXX−XXX optimizing a definite food processing technique in the food production process 31. In our study, the water-soluble protein content was observed to significantly increase (p < 0.05) in flour samples from 0 min (untreated) to 15 min exposure time.The water-soluble protein content was increased from 28.71 to 31.01 mg/g, 23.40 to 25.12 mg/g, 24.93 to 28.38 mg/g, 19.05 to 24.76 mg/g, 17.62 to 20.17 mg/g, and 18.79 to 27.10 mg/g in the case of FS, BS, NS, NGS, CS, and FGS flours, respectively (Table…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…The flax plant's mature fruit is a five-segmented dry boll or capsule. Two seeds are contained in each segment of the boll; hence, a capsule can contain up to 10 (on average 6-8) flaxseeds [9]. Seeds of flax appear in different colors depending on the amount of tannin pigments in the pigment cells of seed coat and included medium, reddish brown, and light yellow, where the brown seeds are the most abundant form of flaxseeds with higher tannin contents [10].…”
Section: Origin and Domesticationmentioning
confidence: 99%